1992
DOI: 10.2307/1542251
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Structure and Function of the Larval Kidney Complex of Prosobranch Gastropods

Abstract: The larval kidneys of prosobranch gastropods have long been assumed to be involved in handling wastes, but with little supporting evidence. In this study, the larval kidneys of Searlesia dira and Nucella canaliculata were studied with light, electron, and fluorescence microscopy. They consist of three cell types: (1) a large external absorptive cell swollen with heterophagosomes and possessing an endocytotically active external surface; (2) an internal crystal cell with numerous vacuole-bound crystals of a cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 48 publications
1
50
1
Order By: Relevance
“…Given that the embryos of this species do not have yolk or other nutrition sources supplied by the parents, it is possible that the increase in the total embryo dry weight was due to consumption of intracapsular material. Previous studies have shown that this behavior is common among encapsulated embryos of gastropod species (De Mahieu et al 1974, Rivest 1992, Rivest & Strathmann 1995, Moran 1999, Ojeda & Chaparro 2004). For example, encapsulated embryos of the indirect developer C. fecunda, and of indirect and direct developer species of the genus Littorina have provided evidence of consumption of capsular material by embryos (Moran 1999, Ojeda & Chaparro 2004).…”
Section: Discussionmentioning
confidence: 80%
“…Given that the embryos of this species do not have yolk or other nutrition sources supplied by the parents, it is possible that the increase in the total embryo dry weight was due to consumption of intracapsular material. Previous studies have shown that this behavior is common among encapsulated embryos of gastropod species (De Mahieu et al 1974, Rivest 1992, Rivest & Strathmann 1995, Moran 1999, Ojeda & Chaparro 2004). For example, encapsulated embryos of the indirect developer C. fecunda, and of indirect and direct developer species of the genus Littorina have provided evidence of consumption of capsular material by embryos (Moran 1999, Ojeda & Chaparro 2004).…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, the experimental treatments (incubation times and albumen concentrations) were only used to gain resolution in microscopical observations (see also Moran, 1999). A solution of bovine serum albumen labelled with commercial fluoroscein isothiocyanate (FITC-BSA, Sigma A9771, Sigma Chemical Co., St Louis, MO, USA) was offered to the embryos (Rivest, 1992;Rivest and Strathmann, 1995). Fluorescence in embryonic organs was taken as evidence of protein intake by embryos and this assumption was based on previous studies showing endocytosis in invertebrate embryos using a scanning electron microscope (Rivest, 1992;Rivest and Strathmann, 1995;Moran, 1999).…”
Section: Fluorescence Microscopymentioning
confidence: 99%
“…A solution of bovine serum albumen labelled with commercial fluoroscein isothiocyanate (FITC-BSA, Sigma A9771, Sigma Chemical Co., St Louis, MO, USA) was offered to the embryos (Rivest, 1992;Rivest and Strathmann, 1995). Fluorescence in embryonic organs was taken as evidence of protein intake by embryos and this assumption was based on previous studies showing endocytosis in invertebrate embryos using a scanning electron microscope (Rivest, 1992;Rivest and Strathmann, 1995;Moran, 1999). Additionally, we observed embryos fed with unlabelled albumen (control) in order to discard the hypothesis of natural fluorescence of embryos when analysing our experimental data using labelled albumen.…”
Section: Fluorescence Microscopymentioning
confidence: 99%
See 2 more Smart Citations